The Impact Of A Modera TE Excercise Programme On Serum Interleukin-2 And Interleukin-4 Levels Among Secondary School Children - MAT LUDIN, ARIMI FITRI (2001)
Cytokines are soluble glycoproteins that mediate cOlntnunication between and within imnlune and non-imtl1une cells. An alteration of cytokine production will impair the ilnrl1Une response and function. Previous studies on the ill1pact of exercise on cytokines have not been conclusive. Most studies were centered on adults and there is a lack of data about the correlation between exercise and cytokines on adolescents. The purpose of this investigation therefore, was to detennine the effect of Illoderate exercise on some cytokine levels in adolescence. Thirty